Agroforestry as a Sustainable Economic Model: Integrating Agriculture and Forestry in Development - Kamaludin, Kamaludin; Sumarni, Sri (PT. Hafasy Dwi Nawasena, 2026)
Agroforestry has emerged as a strategic approach to addressing the dual challenges of environmental degradation and rural economic instability by integrating agricultural and forestry systems within a single land-use framework. This study aims to analyze agroforestry as a sustainable economic model that supports ecological sustainability, economic resilience, and social welfare. The research employs a qualitative approach based on a systematic literature review, utilizing secondary data from peer-reviewed journal articles, scientific reports, and policy documents. Data were analyzed using thematic and interpretative techniques to identify key patterns and relationships among ecological, economic, and institutional dimensions. The results indicate that agroforestry significantly enhances soil fertility, carbon sequestration, biodiversity, and water conservation, while simultaneously providing diversified income sources, improving food security, and strengthening rural livelihoods. Furthermore, institutional support, including policy frameworks, extension services, and community participation, plays a critical role in ensuring successful implementation. The discussion highlights that agroforestry functions not only as a land-use practice but also as an integrated sustainable economic model aligned with Sustainable Development Goals (SDGs). In conclusion, agroforestry offers a holistic and scalable solution for sustainable development, particularly in rural and forest-dependent regions, by balancing environmental conservation with economic productivity.